Giant Lymphatic Malformations in Lower Extremity in an Adult: A Case Report. (December 2018) - Seo, Bommie Florence; Kang, Kyo Joon; Choi, Hyuk Joon; Seo, Kyung Jin; Jung, Sung-No; Shin, Jongweon
Lymphatic malformations are benign vascular malformations rarely seen in adults. There have been only around 100 cases reported in the literature, most of them located in the head and neck area. The etiology is poorly understood but trauma, infection, or tumors have been suggested as possible causes. We present an unusual case of lymphatic malformations in the lower extremity of a 56-year-old male patient after minor trauma. The masses were asymptomatic but progressively enlarged for a period of 2 months, developing into a mass with a 21-cm-long axis in computed tomography images. Total surgical resection was performed and there were no complications or recurrence during the 1-year follow-up period. We present this rare case with a review of relevant previous literatures.